A new genus and species of phytoseiid mite (Acari: phytoseiidae) from the Brazilian Atlantic Forest - Barbosa, Marina Ferraz De Camargo; Rocha, Matheus Dos Santos; Ferla, Noeli Juarez (Zootaxa, 2014)
A new genus, Ingaseius nov. gen., and a new species, Ingaseius silvaticus nov. sp., Phytoseiidae, collected from Inga edulis Martius and Inga marginata Wild. (Fabaceae) are described from the Brazilian Atlantic Forest. This species is unique in the following characteristics: females and males with few teeth on fixed cheliceral digit and short Jv5, without J2, Z1 and leg macrosetae. In addition, females lack Jv3 and Zv3, and have a reduced ventrianal shield.